2004
DOI: 10.1038/sj.hdy.6800444
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ancient genetic subdivision among recently fragmented populations of the endangered shrub Grevillea caleyi (Proteaceae)

Abstract: The genetic effects of population fragmentation cannot be interpreted without understanding the underlying pattern of genetic variation resulting from historic population processes. We used AFLP markers to determine genetic structure and distribution of genetic diversity among populations of an endangered Australian shrub Grevillea caleyi (Proteaceae). Populations that occurred historically on four ridges have new been fragmented to varying degrees, producing some large, relatively pristine populations and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 33 publications
5
57
0
Order By: Relevance
“…Since it is more difficult to measure the Genetic variation in Magnolia stellata populations I Tamaki et al degree of population isolation than population size, good measures for quantifying the degree of population isolation have not yet been established. However, we detected significant relationships between the degree of population isolation and genetic variation, using the number of surrounding populations as the measure of isolation, whereas the distance from the nearest population was used in many previous studies (for example, Llorens et al, 2004;Galeuchet et al, 2005;Lu et al, 2005). Thus, the detection of a significant relationship in this study, and the failure of many of the cited studies to detect such relationship, supports the assertion by Moilanen and Nieminen (2002) that the number of surrounding populations is a much better indicator of isolation than the distance from the nearest population.…”
Section: Factors Influencing the Level Of Within-population Genetic Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is more difficult to measure the Genetic variation in Magnolia stellata populations I Tamaki et al degree of population isolation than population size, good measures for quantifying the degree of population isolation have not yet been established. However, we detected significant relationships between the degree of population isolation and genetic variation, using the number of surrounding populations as the measure of isolation, whereas the distance from the nearest population was used in many previous studies (for example, Llorens et al, 2004;Galeuchet et al, 2005;Lu et al, 2005). Thus, the detection of a significant relationship in this study, and the failure of many of the cited studies to detect such relationship, supports the assertion by Moilanen and Nieminen (2002) that the number of surrounding populations is a much better indicator of isolation than the distance from the nearest population.…”
Section: Factors Influencing the Level Of Within-population Genetic Vmentioning
confidence: 99%
“…The simplest way of doing this is to measure the distance to the nearest population. This approach has been used by various authors (for example, Llorens et al, 2004;Galeuchet et al, 2005;Lu et al, 2005), but few have found significant relationships between this parameter and genetic variation (Lu et al, 2005), probably because it provides a too simplistic indication of isolation (Moilanen and Nieminen, 2002). The cited authors studied possible connectivity measures in spatial ecology and recommended use of a 'buffer measure' based on the number of populations within a given radius around the focal population rather than simply the distance to the nearest population.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of plant species with disjunct distributions have found that genetic diversity is unrelated to census population sizes (Hoebee and Young 2001; Llorens et al. 2004; Leimu and Mutikainen 2005; Mathiasen et al. 2007; Sampson et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, large seed banks can buffer against loss of diversity following population size reduction and inbreeding (Llorens et al. 2004); fitness can be maintained despite high selfing rates through purging of lethals and high seed production (Sampson et al. 2014); self‐incompatibility can promote diversity through multiple paternity in small, dense populations (Llaurens et al.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that our estimate of population size is likely to underestimate the effective population size of these Persoonia species, all of which can develop substantial seedbanks in the soil (Auld et al 2000). A persistent seed-bank provides the opportunity for gene flow over time (between the offspring of multiple cohorts) and can potentially buffer populations against the effects of genetic drift (Llorens et al 2004). Furthermore, there may not have been sufficient time to detect the recent effects of habitat fragmentation (<150 year ago) in these long-lived perennials (Rossetto et al 1995).…”
Section: Does Genetic Variation Relate To Plant Rarity?mentioning
confidence: 99%